Stromboli and the Guns - Gribble, Francis Henry, 1862-1946; Austin, Henry (Salt Lake City, UT : Project Gutenberg, 2013)
"Stromboli and the Guns" by Francis Henry Gribble is a novel written in the early 20th century. It follows the experiences of Jean Antoine Stromboli Kosnapulski, an aging revolutionary, as he recounts his past adventures during significant political upheavals, such as the French Revolution of 1848. The narrative combines elements of historical fiction and dark humor, showcasing the trials and tribulations of a man deeply entwined in the chaotic world of revolutions and conspiracies. At the start of the book, the narrator meets Stromboli in a clandestine anarchist club in London, where the old revolutionary shares his grandiose tales of political turbulence and personal exploits. He speaks of being a key player in pivotal moments of history, claiming responsibility for igniting revolutions and for his daring escapades. The opening sets up an intriguing exploration of Stromboli's past as he prepares to share a specific story from 1848 that highlights his dramatic encounters and the absurdities of revolutionary life. Through vivid descriptions of both the characters and their actions, Gribble introduces readers to a tumultuous world marked by idealism, danger, and the quest for a meaningful legacy amidst chaos. (This is an automatically generated summary.)
Stromboli and the guns -- The short shrift of the filibuster -- The hunted Pole -- The counter revolution -- The man with the ultimatum -- The friend of the policeman -- The secret society -- The visit to the holy man.
Release date is 2013-07-02
Produced by Al Haines
Keywords: Adventure and adventurers -- Fiction; Revolutionaries -- Fiction; Storytellers -- Fiction